A mechanoresponsive PINCH-1-Notch2 interaction regulates smooth muscle differentiation of human placental mesenchymal stem cells. (12th February 2021) - Su, Jie; Guo, Ling; Wu, Chuanyue
Abstract: Extracellular matrix (ECM) stiffness plays an important role in the decision making process of smooth muscle differentiation of mesenchymal stem cells (MSCs) but the underlying mechanisms are incompletely understood. Here we show that a signaling axis consisting of PINCH-1 and Notch2 is critically involved in mediating the effect of ECM stiffness on smooth muscle differentiation of MSCs. Notch2 level is markedly increased in ECM stiffness-induced smooth muscle differentiation of human placental MSCs. Knockdown of Notch2 from human placental MSCs effectively inhibits ECM stiffness-induced smooth muscle differentiation, whereas overexpression of North intracellular domain (NICD2) is sufficient to drive human placental MSC differentiation toward smooth muscle cells. At the molecular level, Notch2 directly interacts with PINCH-1. The interaction of Notch2 with PINCH-1 is significantly increased in response to ECM stiffness favoring smooth muscle differentiation. Furthermore, depletion of PINCH-1 from human placental MSCs reduces Notch2 level and consequently suppresses ECM stiffness-induced smooth muscle differentiation. Re-expression of PINCH-1, but not that of a Notch2-binding defective PINCH-1 mutant, in PINCH-1 knockdown human placental MSCs restores smooth muscle differentiation. Finally, overexpression of NICD2 is sufficient to override PINCH-1 deficiency-induced defect in smooth muscle differentiation. Our results identify an ECM stiffness-responsive PINCH-1-Notch2 interaction that is critically involved in ECM stiffness-induced smooth muscle differentiation of human placental MSCs. Abstract : PINCH-1-Notch2 interaction promotes smooth muscle differentiation in response to mechanical cues from extracellular matrix (ECM). The decision of mesenchymal stem cells to differentiate into smooth muscle cells is influenced by their mechanoenvironment. This study shows that in response to mechanical cues from ECM, PINCH-1 interaction with Notch2 is increased, which inhibits Notch2 degradation and consequently augments Notch2 signaling and smooth muscle differentiation.